Effects of various surfactants on the dispersion stability and electrical conductivity of surface modified graphene - Uddin, Md. Elias; Kuila, Tapas; Nayak, Ganesh Chandra; Kim, Nam Hoon; Ku, Bon-Cheol; Lee, Joong Hee (ELSEVIER SCIENCE SA, 2013)
Ionic and non-ionic surfactant functionalized, water dispersible graphene were prepared to investigate the effects on the dispersion stability and electrical conductivity of graphene. In this study, sodium dodecyl benzene sulfonate (SDBS), sodium dodecyl sulfate and 4-(1,1,3,3-tetramethylbutyl) phenyl-polyethylene glycol (Triton X-100) were used as ionic and non-ionic surfactants. The effects of surfactant concentrations on the dispersibility and electrical conductivity of the surface modified graphene were investigated. The dispersion stability of SDBS functionalized graphene (SDBS-G) was found to be best in water at 1.5 mg ml (1). X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy analysis indicate that the presence of surfactants does not prevent the reduction of graphene oxide (GO). These measurements also demonstrated that the surfactants were present on the surface of graphene, resulting in the formation of functionalized graphene. The thickness of different functionalized graphene was measured by Atomic force microscopy and varied significantly with different surfactants. The thermal properties of the functionalized graphene were also found to be dependent on the nature of the surfactants. The electrical conductivity of SDBS-G (108 S m (1)) was comparatively higher than SDS and Triton X-100 functionalized graphene. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: CHEMICAL-VAPOR-DEPOSITION; REDUCTION; GRAPHITE; CARBON; OXIDE; FUNCTIONALIZATION; COMPOSITE; PHASE